Human exposure to motion during maintenance on floating offshore wind turbines. (1st October 2018) - Scheu, Matti; Matha, Denis; Schwarzkopf, Marie-Antoinette; Kolios, Athanasios
Abstract: Working on floating offshore wind turbines is a complex operation. An important factor is the influence that the structural motion has on humans located on the asset in a harsh environment during maintenance activities and its implications towards personal safety, human comfort and the ability to work. For the research presented in this paper, extensive simulation studies were conducted to assess if and to what extend working on floating offshore wind turbines may be compromised due to extensive structural motion. Results show that weather windows for maintenance activities are reduced by up to 5% when adhering to guidelines suggesting limiting threshold values for acceleration exposure. The corresponding potential financial losses materializing due to longer turbine unavailability after a fault are significant. All the presented and discussed results underline the importance of considering motion criteria in the design phase of a new project - a factor which is not included in design procedures today. Highlights: First time assessment of exposure to motion on FOWTs. Today available standards are used and compared. A novel assessment methodology has been developed, presented and applied. Impact of motion on safety of personnel and workability on the asset is significant. Today applied design practise does not cover this sufficiently. The lack of standards and best practise is substantial.